Interupsi Rizpa: Tafsir Feminis 2 Samuel 21:1-14 - Jelfy L Hursepuny (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
Women’s voices and roles in human civilization often serve as a counter to the dominant power monopolized by men. The voice is prophetic, motherly, and embracing in the face of dominant forces that are often dominant, brutal, and destructive. The purpose of this article is to try to see the meaning of episode II Samuel 21:1-14 which is explored through socio-narrative interpretation with a feminist perspective. From the interpretation done in episode II Samuel 21:1-14 with Rizpah as a passive and sideline figure, it turns out that it can interrupt King David’s brutal and devastating political policies. This interruption supports a feminist movement today to remain critical of those in power who are pro-status quo. Episode I and II Samuel is analyzed first by placing this episode in the socio-political setting of I and II Samuel, then analyzing Rizpah’s role from a feminist perspective and finally looking at Rizpah’s interruption as a model for today’s prophetic voice.